Laser dynamics of a mode-locked thulium/holmium fiber laser in the solitonic and the stretched pulse regimes - Kadel, Rajesh (Kansas State University, 2014)
Mode-locked lasers that produce short optical pulses in the mid-infrared wavelength region have been sought out for a wide range of applications such as free space communication, molecular spectroscopy, medical diagnostics, and remote sensing. Here, a thulium and holmium (Tm/Ho) co-doped fiber laser that mode-locks in both the solitonic and stretched-pulse regimes is used to produce ultra-short pulses in the 2 [mu]m region. Nonlinear polarization rotation technique is used where fiber nonlinearity is responsible to mode-lock the laser. The anomalous group velocity dispersion of both the single mode and gain fibers used limit the laser operation in the solitonic regime where spectral bandwidth is 10 nm and hence the pulse duration is limited to 996 fs. In order to increase the spectral bandwidth and hence get the shorter pulses the anomalous dispersion of these fibers has to compensate using normal group velocity dispersion fiber in the laser cavity. High numerical aperture fibers, which have normal group velocity dispersion around 2 [mu]m due to its large and positive waveguide dispersion, can be used to compensate the anomalous dispersion of the gain and single mode fibers. We used a high numerical aperture fiber called UHNA4 in the laser cavity in order to compensate the anomalous dispersion of other fibers and mode-locked the laser in stretched pulse regime. The spectral bandwidth of the laser increased to 31 nm with corresponding pulse duration of 450 fs measured from the interferometric autocorrelation. The laser dynamics of the Tm/Ho co-doped fiber laser is also studied while going from the stretched-pulse to solitonic regime by fiber cut-back measurements of normal dispersion fiber. It was clearly observed that both the spectral bandwidth and the pulse duration changed significantly going from one region to the other.
Keywords: Mode-locked fiber laser; Physics (0605)